The effect of agitation on the char combustion characteristics of large coal particles - Malik, AA; Pehlivan, D; Howarth, CR (Butterworth-Heinemann Ltd, 1996)
To simulate combustion behaviour in a pilot-scale combustor, a laboratory-scale agitated combustor has been developed which allows burnout and combustion rates for large coal particles to be measured. Particle sizes up to 25 mm can be studied, typical of those used in fixed-bed retorts. Char burnout data were obtained to supplement previously published volatiles release data. A power law relationship between char burnout time, t(b), and particle size, d(p), given by t(b) = k(d)d(p)(n) is proposed, with kd and n as correlation constants. The data were also used to correlate char combustion rates, r(c), for single particles, in the form r(c) = k(r)/d(p)(n').
Keywords: char; combustion characteristics; particle size correlations